(untitled) (Bangladesh Journal of Microbiology, 2019)
The degree of salmonellosis is associated with the genetic diversity of the Salmonella enterica. Here, the genetic diversity of Salmonella enterica isolated from hospital sewage samples of Bangladesh were analyzed to elucidate the prevalence of S. enterica by random amplification of polymorphic DNA (RAPD) and amplified ribosomal DNA restriction analysis (ARDRA). Twenty six isolates were identified as S. enterica by cultural and biochemical methods as well as 16srDNA sequencing. These isolates showed two types of ARDRA and eight distinct RAPD patterns. All of these isolates possessed invA gene. However, agfA and fliC genes were found in 21 isolates and 16 isolates respectively. All of the isolates were resistant to rifamycin but most of them were sensitive to ceftriaxone and streptomycin. The study indicated that the genetic diversity is very high among the S. enterica isolates of Bangladesh. Therefore, such diversity may contribute to the future outbreak of salmonellosis in Bangladesh. Bangladesh J Microbiol, Volume 35 Number 1 June 2018, pp 57-60